P775 Disease activity and treatment patterns of newly diagnosed adult patients with Crohn's disease in Japan: Interim analysis of inception cohort registry study of patients with Crohn's disease (iCREST-CD). (30th January 2023) - Shinzaki, S; Matsuoka, K; Fujii, T; Okamoto, R; Yamada, A; Kunisaki, R; Matsuura, M; Watanabe, K; Shiga, H; Takatsu, N; Bamba, S; Mikami, Y; et al.
Abstract: Background: Biologics are commonly used for the treatment of Crohn's disase (CD); however, the proportion of biologics used and their initiation time from diagnosis differs widely between different regions. There is limited information about the patient characteristics and the treatment persistence of each initial biologics, and the treatment persistence of top-down and step-up therapy. iCREST-CD is a prospective, non-interventional, longitudinal, observational registry study conducted at 19 tertiary centres to understand the characteristics of CD treatments in actual clinical settings in Japan. We conducted an interim analysis (cutoff date: 30 June 2022) of iCREST-CD to mainly evaluate the indication and outcomes of initial biologic therapy. Methods: Patients newly diagnosed with CD after June 2016 based on the diagnostic criteria of the Japanese Guidelines, aged ≥16 years at the time of informed consent with no prior exposure to biologics were enrolled. Patient demographics, clinical data, disease activity and medical treatment were recorded. Biologic use without prior steroid use was defined as top-down and biologic use with prior steroid use was defined as step-up. Results: A total of 672 eligible patients (68.2% male) with mean age (±SD) of 29.4 (13.1) years were analysed. Cumulative proportion of patients prescribed 5-aminosalicylic acid, steroids, immunomodulators, and biologics at 6- and 12-months from diagnosis were 71.3%, 40.6%, 31.4%, and 47.5%; and 75.0%, 43.6%, 36.0%, and 59.7%, respectively (Figure 1). A total of 498 patients received biological therapy—infliximab (IFX; 121 [24.3%]), adalimumab (ADA; 244 [49.0%]), ustekinumab (UST; 107 [21.5%]), and vedolizumab (VDZ; 26 [5.2%]). The mean age (±SD) at the initiation of biologic treatment was IFX: 28.2 (11.3), ADA: 26.6 (10.8), UST: 30.4 (14.1), and VDZ: 36.2 (17.4), and the mean (±SD) levels of C-reactive protein (CRP) (mg/L) was IFX: 25.9 (26.8), ADA: 18.9 (26.0), UST: 13.5 (17.9), and VDZ: 9.5 (19.0) (Table.1). The initial biologic treatment persistence rates of IFX, ADA, UST and VDZ at 36-months were 77.5%, 75.8%, 79.8%, and 49.0%, respectively (Figure 2). Patients receiving top-down and step-up therapy were 284 (57.0%) and 214 (43.0%), respectively. The treatment persistence rate of initial biologics by top-down and step-up therapy at 36-months from diagnosis was 81.6% and 66.9%, respectively (P=0.001) (Figure 3). Conclusion: This registry study that demonstrated the treatment persistence rate of initial biologic therapy was significantly higher in the top-down than the step-up approach.